Green tea polyphenol epigallocatechin-3-gallate (EGCG) as adjuvant in cancer therapy - Lecumberri, Elena; Dupertuis, Yves Marc; Miralbell, Raymond; Pichard, Claude (Clinical nutrition (Edinburgh, Scotland), 2013)
Green tea catechins, especially epigallocatechin-3-gallate (EGCG), have been associated with cancer prevention and treatment. This has resulted in an increased number of studies evaluating the effects derived from the use of this compound in combination with chemo/radiotherapy. This review aims at compiling latest literature on this subject. Keywords including EGCG, cancer, chemotherapy, radiotherapy and side effects, were searched using PubMed and ScienceDirect databases to identify, analyze, and summarize the research literature on this topic. Most of the studies on this subject up to date are preclinical. Relevance of the findings, impact factor, and date of publication were critical parameters for the studies to be included in the review. Additive and synergistic effects of EGCG when combined with conventional cancer therapies have been proposed, and its anti-inflammatory and antioxidant activities have been related to amelioration of cancer therapy side effects. However, antagonistic interactions with certain anticancer drugs might limit its clinical use. The use of EGCG could enhance the effect of conventional cancer therapies through additive or synergistic effects as well as through amelioration of deleterious side effects. Further research, especially at the clinical level, is needed to ascertain the potential role of EGCG as adjuvant in cancer therapy.